17-Hydroxyprogesterone Caproate Significantly Improves Clinical Characteristics of Preeclampsia in the Reduced Uterine Perfusion Pressure Rat Model. Issue 1 (January 2015) - Amaral, Lorena M.; Cornelius, Denise C.; Harmon, Ashlyn; Moseley, Janae; Martin, James N.; LaMarca, Babbette
<x xml:space="preserve">Abstract</x> Preeclampsia is characterized by increased uterine artery resistance index, chronic immune activation, and decreased circulating nitric oxide levels. 17-α-Hydroxyprogesterone caproate (17-OHPC) is a synthetic metabolite of progesterone used for the prevention of recurrent preterm birth. We hypothesized that 17-OHPC could reduce mean arterial pressure by decreasing inflammation, whereas improving vasodilation by increasing nitric oxide bioavailability and uterine artery resistance index during late gestation in the reduced uterine perfusion pressure (RUPP) rat model of preeclampsia. 17-OHPC (3.32 mg/kg) was intraperitoneally administered on gestation day 18 into RUPP rats, carotid catheters inserted, and mean arterial pressure, blood, and tissues were collected on day 19. Mean arterial pressure in normal pregnant (NP; n=13) was 92±2.0 and increased to123±2.0 in RUPP (n=18; P<0.0001), which was improved to 116±1.5 mm Hg in RUPP+17-OHPC (n=10; P<0.05). Circulating CD4+ T cells were 1.19%±1.0% of gated cells in NP (n=7), which increased to 8.52%±2.4% in RUPP rats (n=10; P<0.05) but was reduced to 2.72%±0.87% (n=14; P<0.05) in RUPP+17-OHPC. Circulating nitrate/nitrite was 26.34±3.5 µmol/L in NP (n=12) but was reduced to14.58±3.1 in RUPP rats (n=8; P=0.03) and increased to 22.69±1.62 in RUPP+17-OHPC (n=7; P=0.05). Endothelial nitric oxide synthase expression was 0.65±0.11 AU in NP (n=4), which decreased to 0.33±0.01 in RUPP rats (n=4; P=0.05) but increased to 0.57±0.01 in RUPP+17-OHPC (n=5; P=0.03). Uterine artery resistance index was 0.54±0.02 in NP (n=3), 0.78±0.03 in RUPP (n=4), and 0.63±0.038 in RUPP+17-OHPC (n=8; both P<0.05). Our findings demonstrate that even though modest, lowering blood pressure with 17-OHPC could be a viable treatment option for suppressing inflammation, uterine artery vasoconstriction while improving litter size.